Characterization of hemoglobin immobilized on gamma-zirconium phosphate - Geng, LN; Wang, X; Li, N; Xiang, MH; Li, KA (Colloids and Surfaces B: Biointerfaces, 2004)
The fact that different gamma-zirconium phosphate (gamma-ZrP) preintercalation method induced varied degree and type of conformational change of the adsorption protein was confirmed by characterization techniques including circular dichroism (CD), fourier transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD) analysis. The results indicated that the association of hemoglobin with gamma-ZrP preintercalated using butylamine was correlated with conformational change in the secondary structure of the protein. gamma-ZrP which was preintercalated with tetra (n-butylammonium) hydroxide caused the conformational change of Hemoglobin in both the secondary structure and the tertiary structure. X-ray powder diffraction analysis was used to analyze the crystalline Structure of the nanocomposites prepared by relamination. The adsorption isotherms of Hemoglobin on different matrices were set LIP and fitted with Langmuir and Freundlich equations. (C) 2004 Published by Elsevier B.V. Biophysics Chemistry, Physical Materials Science, Biomaterials SCI(E) EI PubMed 14 ARTICLE 4 231-238 34